The Development of New Clinical Legal Education Courses at the Faculty of Law, Hasanuddin University, Makassar- Indonesia: Challenges and Prospects - Maskun, Maskun (Hasanuddin University, 2015)
Clinical subjects are a new model in Faculty of Law Hasanuddin Universityâs curriculum. It currently is implementing four legal clinics: (1) a civil law clinic; (2) a criminal law clinic; (3) an anti-corruption law clinic; and (4) an environmental law clinic. All of these clinics have been adopted in FH-UNHASâs curriculum. This paper will focus on those subjects as new clinics and the students as new clinicians. It also discusses many challenges we face in managing the clinics and ensuring that all clinic students are able to engage in quality programming while working with our partners (local civil society organizations [CSOs] and formal justice institutions, such as District Courts and Provincial Prosecutor Offices).